Preparation and application of carbon-loaded PtCo ordered structure oxygen reduction electrocatalyst
The preparation of carbon-supported PtCo ordered structure oxygen reduction electrocatalysts was solved by step-by-step reduction method, which solved the problems of metal dissolution and structural instability of platinum-based catalysts in fuel cells, and achieved efficient catalytic activity and stability of oxygen reduction reactions. It is suitable for Fuel cell technology.
Patent Information
- Application Number
- CN202411326565.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
Platinum-based catalysts are prone to metal dissolution and structural instability problems in fuel cells, resulting in catalytic activity attenuation and limiting the commercialization progress of fuel cells.
The carbon-supported PtCo ordered structure oxygen reduction electrocatalyst was prepared by step-by-step reduction method, and the Co/C support was prepared by sodium borohydride reduction method, Pt salt was impregnated, and the PtCo intermetallic compound on conductive carbon black was formed by high-temperature gas reduction method. A dense platinum shell is formed to prevent the transition metal from dissolution.
The prepared catalyst has small particles, uniform distribution, high thermal stability, and excellent catalytic activity of oxygen reduction reaction. It is suitable for fuel cell technology, reducing the amount of platinum used and improving the stability of the catalyst.
Smart Images

Figure CN119208638A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to the preparation and application of a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst. Background Art
[0002] As an environmentally friendly energy source, fuel cell technology can effectively reduce the use of fossil energy, reduce carbon dioxide emissions, and achieve the "dual carbon" goal. In today's energy-intensive situation, it has attracted the attention of academia and industry around the world. Catalysts are key materials for realizing fuel cell technology. Their catalytic efficiency determines the efficiency of fuel cells. In addition, their cost is also a constraint on the development of fuel cell technology. Researching high-efficiency catalysts, optimizing the synthesis steps, and making this catalyst preparation method suitable for large-scale preparation are key technologies to improve their performance and durability and reduce catalyst costs.
[0003] Based on the high catalytic activity of platinum, the precious metal Pt is still the main catalyst used in water electrolysis to produce hydrogen, direct alcohol fuel cells and hydrogen fuel cells. However, pure Pt catalysts are prone to agglomeration, dissolution and poisoning during the actual operation of fuel cells, resulting in unsatisfactory utilization of platinum atoms, which seriously restricts the commercialization progress of fuel cells. Researchers have found that the use of Pt with other metal elements can not only reduce the amount of Pt used but also improve its activity and durability.
[0004] For the solid solution alloy formed by Pt and transition metals, a large amount of alloy atoms are dissolved after long-term use, which causes the coordination number of surface Pt atoms to drop rapidly and the surface atoms to rearrange, resulting in a sharp decline in its catalytic activity. In order to inhibit the dissolution of transition metals during the reaction, it is necessary to increase the interaction force between Pt atoms and transition metal atoms, and form a dense platinum shell on the outer surface of alloy nanoparticles to prevent the segregation of transition metal atoms to the surface. Platinum-based ordered alloys (i.e., intermetallic compound alloys) have a highly ordered arrangement of Pt atoms and transition metal atoms, and the interaction force is stronger than that of solid solution alloys, and theoretically have stronger corrosion resistance. Therefore, the development of highly dispersed, small-sized platinum-based ordered alloy catalysts is of great significance to reduce the amount of catalyst platinum used and improve the catalytic activity and stability of platinum-based catalysts. Summary of the invention
[0005] In view of this, the purpose of the present invention is to overcome the shortcomings of metal dissolution and structural instability of platinum-based catalysts in actual use, and to provide a preparation and application of a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst. The present invention adopts a step-by-step reduction method, firstly adopts a sodium borohydride reduction method to prepare a Co / C precursor, then combines Pt with Co / C by an impregnation method, and finally uses a high-temperature gas reduction method to prepare a Pt-based ordered structure catalyst supported on conductive carbon black. The method is simple to operate and has a low preparation temperature, and can be used for industrial mass production. The prepared catalyst particles are uniformly distributed, small in size, and have high catalytic activity in oxygen reduction reactions.
[0006] To achieve the above object, the technical solution of the present invention is as follows:
[0007] A method for preparing a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst comprises the following steps:
[0008] Step 1: dispersing conductive carbon black in distilled water to obtain a conductive carbon black dispersion; dissolving cobalt salt in distilled water to obtain a cobalt salt solution;
[0009] Step 2: After the cobalt salt solution and the conductive carbon black dispersion are evenly mixed, a reducing agent is added to react;
[0010] Step 3: Drying and grinding the precipitate obtained by the reaction to obtain Co / C powder;
[0011] Step 4: Disperse Co / C powder in chloroform, add platinum acetylacetonate, stir and heat, remove chloroform, and obtain a mixture of platinum salt and Co / C;
[0012] Step 5: placing the platinum salt and Co / C mixture in a reducing gas atmosphere for heat treatment to obtain PtCo / C intermetallic compound powder;
[0013] Step 6: The PtCo / C intermetallic compound powder is dissolved in a mineral acid, stirred overnight, and then washed, centrifuged, and vacuum dried overnight to obtain a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst.
[0014] Furthermore, in step 1, the conductive carbon black is ECP600 JD, and the cobalt salt is cobalt chloride or cobalt sulfate.
[0015] Furthermore, in step 2, the reducing agent is sodium borohydride, and after the cobalt salt solution and the conductive carbon black dispersion are evenly mixed, the mass percentage of cobalt to carbon is 10%.
[0016] Furthermore, the drying conditions in step 3 are: first vacuum drying for 6 hours, and then drying at 120° C. for 4 hours under Ar atmosphere.
[0017] Furthermore, the amount of platinum acetylacetonate added in step 4 is calculated based on a mass ratio of Pt to Co of 1:2; the stirring speed is 800-900 rpm, the heating time is 3 h, and the heating temperature is 65-70 ° C; the method for removing chloroform is heating volatilization drying (the amount of chloroform is less than 15 mL) or rotary evaporation (the amount of chloroform is greater than 15 mL).
[0018] Furthermore, in step 5, the reducing gas is a hydrogen / argon mixture with a volume ratio of 1:9, and a gas flow rate of 20-25 mL / min; the heat treatment temperature is 900° C., the time is 1.5 h, and the heating rate is 10° C. / min.
[0019] Furthermore, in step 6, the mineral acid is nitric acid.
[0020] An electrode catalyst for a fuel cell comprises a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst prepared by the method described above.
[0021] A fuel cell electrode comprises a catalyst layer containing the fuel cell electrode catalyst described above.
[0022] A fuel cell comprises the fuel cell electrode as described above.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The catalyst is prepared by a step-by-step reduction method. First, a Co / C carrier is prepared at room temperature using sodium borohydride, then a Pt salt is impregnated, and finally a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst is prepared by high-temperature gas reduction. The preparation method is green and simple and can be prepared in batches.
[0025] (2) The catalyst particles are small, uniform in size, and have high thermal stability;
[0026] (3) The catalyst has good catalytic performance for oxygen reduction reaction and can be used in the field of fuel cell technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the XRD characterization result of the catalyst prepared in Example 1 of the present invention.
[0028] Figure 2 This is the TEM characterization result of the catalyst prepared in Example 1 of the present invention.
[0029] Figure 3 This is the cyclic voltammetry test result of the catalyst prepared in Example 1 of the present invention in a N2-saturated 0.1M HClO4 electrolyte.
[0030] Figure 4This is the test result of the polarization curve of the catalyst prepared in Example 1 of the present invention in an O2-saturated 0.1M HClO4 electrolyte.
[0031] Figure 5 This is the test result of the catalyst prepared in Example 1 of the present invention after 30,000 cycles. DETAILED DESCRIPTION
[0032] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0033] Example 1
[0034] (1) Catalyst preparation
[0035] Weigh 90 mg of conductive carbon black ECP600 JD into a beaker, add 20 mL of distilled water, and stir vigorously for 20 minutes.
[0036] Weigh 40.45 mg of CoCl2·6H2O into another beaker, add 5 mL of distilled water and ultrasonically dissolve it, mix it with the dispersed conductive carbon black ECP600 JD, and continue stirring for 30 minutes to allow CoCl2·6H2O to be fully adsorbed on the conductive carbon black ECP600 JD.
[0037] After sufficient stirring, add 1mL of 0.3mol / L NaBH4 aqueous solution with a pH of 9 to ensure that the cobalt ions are completely converted into the metallic state. Stir for 3 hours and collect the precipitate by centrifugation. Wash the excess NaBH4 with distilled water and centrifuge again. Drying First use vacuum drying for 6 hours to remove most of the moisture, then put it into a tube furnace and dry it at 120℃ under Ar atmosphere for 4 hours. After taking it out, grind it to obtain a dry powder, which is recorded as 10% Co / C.
[0038] 10% Co / C powder was placed in a 20mL ampoule, and 10mL chloroform was added, and ultrasonic dispersion was performed for 10 minutes. 10mg of acetylacetonate platinum (Pt(acac)2) was weighed and added to the ampoule, where the mass ratio of Pt to Co was 1:2, and ultrasonic dissolution was performed. Then magnetic stirring was used for 3h, the temperature was set to 70°C, the speed was 900rpm, and the bottle mouth was wrapped with aluminum foil with small holes until the chloroform evaporated to dryness, and the metal precursor powder was obtained.
[0039] The metal precursor powder was transferred into a quartz boat and placed in a tube furnace. The mixture was ventilated with 10% H2 / 90% Ar (volume ratio) for 30 minutes to drive out the air in the furnace. The gas flow rate was 20 mL / min, and the heating rate was set to 10°C / min. The mixture was calcined at 900°C for 1.5 hours. Pt was reduced with H2 and alloyed with Co at high temperature. The calcined powder was dissolved in 5 mL of 0.1 M dilute nitric acid, acid-washed and stirred overnight. Afterwards, the mixture was washed with a mixed solution of distilled water and ethanol, centrifuged, and vacuum dried overnight.
[0040] (2) Catalyst structure characterization
[0041] The XRD data of the prepared catalyst are shown in Figure 1 It can be clearly seen that the prepared catalyst overlaps with the standard fctPtCo ordered structure card. Figure 2 The transmission electron microscopy characterization shows that the size of the prepared catalyst is about 3-4nm, the diffraction fringes fct PtCo (111) crystal plane spacing 0.219nm overlap, and the ICP analysis results show that the atomic ratio of Pt and Co in the prepared catalyst is 56.3:43.7. Therefore, the prepared catalyst is an fct PtCo ordered structure, belonging to L 10 Phase PtCo intermetallic compound.
[0042] (3) Catalyst performance evaluation
[0043] The catalyst performance was evaluated by using a rotating disk electrode for electrochemical activity and stability testing. The test conditions were a three-electrode test system, with a glassy carbon electrode (d = 5.0 mm) (area 0.196 cm 2 ) as the working electrode of the disk, saturated calomel electrode as the corresponding reference electrode, the reference electrode is connected to the Luggin capillary to reduce the liquid junction potential and protect the reference electrode, and the platinum sheet is used as the corresponding counter electrode. The electrolyte used is 0.1M perchloric acid.
[0044] Weigh 2 mg of catalyst sample, add 500 μL isopropanol, 500 μL distilled water and 5 μL 5wt% Nafion solution, and disperse at low temperature for about 1.5 hours to make a uniform catalyst mixed slurry. Take a certain volume of catalyst mixed slurry and drop it on the surface of the working electrode (glassy carbon electrode with d = 5.0 mm). After the catalyst mixed slurry is naturally dried to form a film, the electrochemical activity and stability test is carried out.
[0045] The CV test was carried out in a N2-saturated 0.1M HClO4 electrolyte, with a potential scan range of 0.1-1.1Vvs RHE and a scan rate of 50mV / s. The electrochemically active area ECSA of the electrode catalyst can be calculated according to the calculation formula. The electrochemically active area is an important parameter for evaluating the number of active sites and area specific activity of the catalyst, and is related to the catalytic performance of the catalyst. Figure 3 The electrochemical CV curve of Example 1 is shown in Figure 1. According to the geometric area of the hydrogen adsorption region (0.1-0.4 V interval) of the Pt catalyst, the electrochemical active area ECSA of the PtCo catalyst is calculated to be 23.6 m 2 g Pt -1 , lower than the commercial PtC's 42.2m 2 g Pt -1 Electrochemical active area, which is due to the incorporation of Co into the Pt lattice, affecting the amount of hydrogen adsorption on the Pt catalyst.
[0046] LSV test was carried out in O2 saturated 0.1M HClO4 electrolyte, with LSV scan at 20mV / s scan rate, scan range 0.2-1.1V vs RHE, and rotating disk electrode speed 1600rpm. The half-wave potential (E1 / 2), mass activity (MA), and Tafel slope can be obtained from the polarization curve to evaluate the oxygen reduction activity performance. Figure 4 The LSV test results of the fct PtCo catalyst prepared in Example 1 are as follows. Figure 4 It can be concluded that the half-wave potential of oxygen reduction of the fct PtCo catalyst is 0.913V, which is higher than the half-wave potential of the commercial JM-Pt / C catalyst (0.877V). The higher the half-wave potential in the oxygen reduction reaction, the closer it is to the equilibrium potential, the smaller the overpotential at the same current density, and the easier it is to carry out the oxygen reduction reaction. The value of the Tafel slope reflects the kinetic characteristics of the reaction, that is, the reactions with different Tafel slopes have different rate-controlling steps. In the oxygen reduction reaction, a smaller Tafel slope means a faster kinetic process, indicating that the catalyst can reach the desired current at a lower overpotential. The Tafel slope of the fct PtCo catalyst prepared in Example 1 is 75.8mV dec. -1 , which is less than 102.2mV dec of commercial JM-Pt / C -1, further indicating that the prepared catalyst has superior performance. The mass activity depends largely on the size of the electrocatalyst particles (i.e., the number of active sites). The mass activity is obtained by normalizing the current density to the loaded mass of the electrocatalyst. It can be used as a reasonable parameter to evaluate the intrinsic performance of different electrode materials during the oxygen reduction reaction. The definition of mass activity assumes that all atoms in each particle are electrocatalytically active sites. The mass specific activity of the fctPtCo catalyst prepared in Example 1 is 0.84A mgPt -1 , is a commercial JM-Pt / C (0.15A mgPt -1 ) is 5.6 times.
[0047] The stability test was carried out in an O2-saturated 0.1M HClO4 electrolyte. The voltage range was set to 0.6-1.0Vvs RHE and the scan rate was 100mV / s. CV uninterrupted scanning was performed as an accelerated stability test (ADT). The changes in the CV and LSV curves before and after the scan were observed, and the performance of the obtained catalyst was evaluated.
[0048] Figure 5 The stability data of the electrocatalyst prepared in Example 1 are shown. After 30,000 cycles of accelerated scanning, the mass activity of the prepared catalyst increased from the initial 0.84A mgPt -1 Down to 0.72A mgPt -1 , only decayed by 14.3%, while JM-Pt / C decayed from the initial 0.15A mgPt -1 Down to 0.05A mgPt -1 , which was attenuated by 66.6%. In summary, the fct PtCo ordered structure oxygen reduction electrocatalyst prepared in Example 1 has excellent electrocatalytic performance.
[0049] Example 2
[0050] Weigh 450 mg of conductive carbon black ECP600 JD into a beaker, add 100 mL of distilled water, and stir vigorously for 20 minutes.
[0051] Weigh 200 mg of CoCl2·6H2O into another beaker, add 50 mL of distilled water and ultrasonically dissolve it, mix it with the dispersed conductive carbon black ECP600 JD, and continue stirring for 30 minutes to allow CoCl2·6H2O to be fully adsorbed on the conductive carbon black ECP600 JD.
[0052] After sufficient stirring, add 5mL of 0.3mol / L NaBH4 aqueous solution with a pH of 9 to ensure that the cobalt ions are completely converted into the metallic state. Stir for 4 hours and collect the precipitate by centrifugation. Wash the excess NaBH4 with distilled water and centrifuge again. Drying First use vacuum drying for 6 hours to remove most of the moisture, then put it into a tube furnace and dry it at 120℃ under Ar atmosphere for 4 hours. After taking it out, grind it to obtain a dry powder, which is recorded as 10% Co / C.
[0053] 10% Co / C powder was placed in a 100mL single-neck round-bottom flask, and 50mL chloroform was added, and ultrasonic dispersion was performed for 10 minutes. 50mg of acetylacetonate platinum (Pt(acac)2) was weighed and added to a single-neck round-bottom flask, where the mass ratio of Pt to Co was 1:2, and ultrasonic dissolution was performed. Then magnetic stirring was used for 3h, the temperature was set to 70°C, the speed was 900rpm, and the bottle mouth was wrapped with aluminum foil with small holes. After the stirring was completed, the non-volatile chloroform was removed by rotary evaporation to obtain a metal precursor powder.
[0054] The metal precursor powder was transferred into a quartz boat and placed in a tube furnace. The mixture was ventilated with 10% H2 / 90% Ar (volume ratio) for 30 minutes to drive out the air in the furnace. The gas flow rate was 22 mL / min, and the heating rate was set to 10°C / min. The mixture was calcined at 900°C for 1.5 hours. Pt was reduced with H2 and alloyed with Co at high temperature. The calcined powder was dissolved in 5 mL of 0.1 M dilute nitric acid, acid-washed and stirred overnight. Afterwards, the mixture was washed with a mixed solution of distilled water and ethanol, centrifuged, and vacuum dried overnight.
[0055] The catalyst characterization was the same as in Example 1.
[0056] Example 3
[0057] Weigh 900 mg of conductive carbon black ECP600 JD into a beaker, add 300 mL of distilled water, and stir vigorously for 20 minutes.
[0058] Weigh 404.5 mg of CoCl2·6H2O into another beaker, add 50 mL of distilled water and ultrasonically dissolve it, mix it with the dispersed conductive carbon black ECP600 JD, and continue stirring for 30 minutes to allow CoCl2·6H2O to be fully adsorbed on the conductive carbon black ECP600 JD.
[0059] After sufficient stirring, add 10mL of 0.3mol / L NaBH4 aqueous solution with a pH of 9 to ensure that the cobalt ions are completely converted into the metallic state. Stir for 4 hours and collect the precipitate by centrifugation. Wash the excess NaBH4 with distilled water and centrifuge again. Drying First use vacuum drying for 6 hours to remove most of the moisture, then put it into a tube furnace and dry it at 120℃ under Ar atmosphere for 4 hours. After taking it out, grind it to obtain a dry powder, which is recorded as 10% Co / C.
[0060] 10% Co / C was placed in a single-neck round-bottom flask with a volume of 250 mL, and 150 mL of chloroform was added, and ultrasonic dispersion was performed for 10 min. Subsequently, 100 mg of acetylacetonate platinum (Pt(acac)2) was weighed and added to the single-neck round-bottom flask, where the mass ratio of Pt to Co was 1:2. Then, magnetic stirring was used for 3 h, the temperature was set to 70 ° C, the speed was 900 rpm, and the bottle mouth was wrapped with aluminum foil with small holes. After the stirring was completed, the remaining chloroform was removed by rotary evaporation to obtain a metal precursor powder.
[0061] The metal precursor powder was transferred into a quartz boat and placed in a tube furnace. It was first ventilated with a 10% H2 / 90% Ar (volume ratio) mixed gas for 30 minutes to drive out the air in the furnace. The gas flow rate was 25 mL / min, and the heating rate was set to 10°C / min. It was calcined at 900°C for 1.5 hours. Pt was reduced with H2 and alloyed with Co at high temperature. The calcined powder was dissolved in 30 mL of 0.1 M dilute nitric acid, acid-washed and stirred overnight. It was then washed with a mixed solution of distilled water and ethanol, centrifuged, and vacuum dried overnight.
[0062] The catalyst characterization was the same as in Example 1.
[0063] The above description is only for better explaining the embodiments of the present invention, and is not intended to limit the present invention. Any modification or equivalent substitution that does not depart from the spirit and scope of the present invention shall fall within the scope of the present invention.
Claims
1. A method for preparing a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst, characterized in that: The following steps are involved: Step 1: dispersing conductive carbon black in distilled water to obtain a conductive carbon black dispersion; dissolving cobalt salt in distilled water to obtain a cobalt salt solution; Step 2: After the cobalt salt solution and the conductive carbon black dispersion are evenly mixed, a reducing agent is added to react; Step 3: Drying and grinding the precipitate obtained by the reaction to obtain Co / C powder; Step 4: Disperse Co / C powder in chloroform, add platinum acetylacetonate, stir and heat, remove chloroform, and obtain a mixture of platinum salt and Co / C; Step 5: placing the platinum salt and Co / C mixture in a reducing gas atmosphere for heat treatment to obtain PtCo / C intermetallic compound powder; Step 6: The PtCo / C intermetallic compound powder is dissolved in a mineral acid, stirred overnight, and then washed, centrifuged, and vacuum dried overnight to obtain a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst.
2. The method for preparing a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst according to claim 1, characterized in that: In the step 1, the conductive carbon black is ECP600 JD, and the cobalt salt is cobalt chloride or cobalt sulfate.
3. The method for preparing a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst according to claim 1, characterized in that: In the step 2, the reducing agent is sodium borohydride, and after the cobalt salt solution and the conductive carbon black dispersion are evenly mixed, the mass percentage of cobalt and carbon is 10%.
4. The method for preparing a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst according to claim 1, characterized in that: The drying conditions in step 3 are: first vacuum drying for 6 hours, and then drying at 120° C. for 4 hours under Ar atmosphere.
5. The method for preparing a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst according to claim 1, characterized in that: The amount of platinum acetylacetonate added in step 4 is calculated based on a mass ratio of Pt to Co of 1:2; the stirring speed is 800-900 rpm, the heating time is 3 hours, and the heating temperature is 65-70° C.; and the method for removing chloroform is heating volatilization drying or rotary evaporation.
6. The method for preparing a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst according to claim 1, characterized in that: In step 5, the reducing gas is a hydrogen / argon mixture with a volume ratio of 1:9, and the gas flow rate is 20-25 mL / min; the heat treatment temperature is 900° C., the time is 1.5 h, and the heating rate is 10° C. / min.
7. The method for preparing a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst according to claim 1, characterized in that: In step 6, the mineral acid is nitric acid.
8. A fuel cell electrode catalyst, characterized in that: The invention comprises a carbon-supported PtCo ordered structure oxygen reduction electrocatalyst prepared by the method according to any one of claims 1 to 7.
9. A fuel cell electrode, characterized in that: A catalyst layer comprising the fuel cell electrode catalyst according to claim 8 is provided.
10. A fuel cell, characterized in that: A fuel cell electrode according to claim 9.
Citation Information
Cited By
Nb-oxygen fluorine cluster confinement and pulse induction ordering-based oxygen reduction catalyst and preparation method and application thereof
CN122025676A
